Family, Taboo and Communism in Poland, 1956-1989 - Klich-Kluczewska, Barbara (Polish Studies - Transdisciplinary Perspectives, 2021)
The book answers fundamental questions about the processes of social negotiation of mentality shifts in communist Poland. Taking divorce, single motherhood, domestic violence and abortion as examples, it analyzes the level of acceptance toward tabus grounded in tradition, and the course of negotiating new meanings and using social exclusion when dealing with new phenomena. The author uses not only national documents, but also ego-documents and cultural texts to prove the macrosocietal dictatorship in the years 1956-1989 contributed not to the revolutionization of society at the family level, but to its perpetuation. The family references made by the communist authorities, especially in the last two decades of their regime, can be treated as one of the factors legitimizing the system.